STUDI TUMBUHAN BERKHASIAT OBAT PADA SUKU DONDO DI KECAMATAN OGODEIDE, KABUPATEN TOLITOLI, PROVINSI SULAWESI : Study of Drug Effective Plants on The Dondo Tribe in Ogodeide District, Tolitoli Regency, Central Sulawesi Province - Syariful Anam; Agustinus Widodo; Muhamad Rinaldhi Tandah (Biocelebes, 2022)
The Dondo Tribe is an indigenous tribe in Ogodeide District. The Dondo Tribe still uses traditional medicine to treat various diseases. The high trust of the Dondo people towards the use of traditional medicine makes people prefer to use traditional medicine. This study aimed to determine the types, parts, and methods of use of plants that have been used as traditional medicine by the bolrians of the Dondo tribe, Ogodeide District, Tolitoli Regency, Central Sulawesi Province. This type of research was descriptive qualitative and the sampling technique was purposive sampling, with structured interview techniques on 11 informants by filling out questionnaires with supporting documentation. The results of the study found that as many as 40 species of plants used as traditional medicine by the bolrians of the Dondo tribe in Ogodeide District which are still preserved today. The percentages of the most widely used plant parts were leaves 55%, stems 11%, rhizomes 11%, roots 5%, fruit 5%, herbs 5%, bark 2%, twigs 2%, tubers 2% and flowers 2%. The percentage of how to use plants as traditional medicine is 65% taken, 26% affixed, 3% seen, 3% washing and 3% smeared.